High‐throughput quantification of drugs of abuse in biofluids via 96‐solid‐phase microextraction–transmission mode and direct analysis in real time mass spectrometry. (6th August 2019) - Vasiljevic, Tijana; Gómez‐Ríos, Germán Augusto; Li, Frederick; Liang, Paul; Pawliszyn, Janusz
Abstract : Rationale: The workload of clinical laboratories has been steadily increasing over the last few years. High‐throughput (HT) sample processing allows scientists to spend more time undertaking matters of critical thinking rather than laborious sample processing. Herein we introduce a HT 96‐solid‐phase microextraction (SPME) transmission mode (TM) system coupled to direct analysis in real time (DART) mass spectrometry (MS). Methods: Model compounds (opioids) were extracted from urine and plasma samples using a 96‐SPME‐TM device. A standard voltage and pressure (SVP) DART source was used for all experiments. Examination of SPME‐TM performance was done using high‐resolution mass spectrometry (HRMS) in full scan mode (100–500 m/z ), whereas quantitation of opioids was performed using triple quadrupole MS in multiple reaction monitoring mode and by using a matrix‐matched internal standard correction method. Results: Thirteen points (0.5 to 200 ng mL −1 ) were used to establish a calibration curve. Low limits of quantitation (LOQ) were obtained (0.5 to 25 ng mL −1 ) for matrices used. Acceptable accuracy (71.4–129.4%) and repeatability (1.1–24%) were obtained for validation levels tested (0.5, 30 and 90 ng mL −1 ). In less than 1.5 hours, 96 samples were extracted, desorbed and processed using the 96‐SPME‐TM system coupled to DART‐MS. Conclusions: A rapid HT method for detection of opioids in urine and plasma samples was developed. This study demonstrated that ambient ionization mass spectrometry coupled to robust sample preparation methods such as SPME‐TM can rapidly and efficiently screen/quantify target analytes in a HT context.